Compact binary populations in globular clusters and prospects for gravitational wave detection - Downing, Jonathan Michael Blake (2009)
The inspiral and merger of compact binary stars will be major detection events for interferometric gravitational wave observatories. These observatories operate most effectively by comparing their output to template waveforms. In order to make these templates the physical parameters of the source population must be understood. Compact binaries in the galactic field have been investigated using population synthesis models but in dense stellar environments interactions can alter the binary population and may enhance the merger rate ...
Keywords: Hochschulschrift; Monte-Carlo-Simulation; Gravitationswellendetektor